2015
DOI: 10.1042/bst20150171
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)-binding proteins and mRNA localization: who rules the roost?

Abstract: RNA-binding proteins are often multifunctional, interact with a variety of protein partners and display complex localizations within cells. Mammalian cytoplasmic poly(A)-binding proteins (PABPs) are multifunctional RNA-binding proteins that regulate multiple aspects of mRNA translation and stability. Although predominantly diffusely cytoplasmic at steady state, they shuttle through the nucleus and can be localized to a variety of cytoplasmic foci, including those associated with mRNA storage and localized tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 70 publications
2
52
1
3
Order By: Relevance
“…Intriguingly, PABP is relocalized to the nucleus in an ICP27-independent manner at late times postinfection (10,11), suggesting that ICP27 may provide a means to direct limiting amounts of cytoplasmic PABP to a subset of viral mRNAs late in infection (7,8). Moreover, because PABP nuclear export is largely mRNA-driven in mammalian cells (12), and ICP27 promotes export of viral mRNAs (17), it is possible that the ICP27-PABP interaction may allow nuclear-retained PABP to be recruited and exported on these mRNAs, enabling their efficient translation. Specific binding of ICP27 to mRNAs that it translationally activates may be aided by another viral factor (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, PABP is relocalized to the nucleus in an ICP27-independent manner at late times postinfection (10,11), suggesting that ICP27 may provide a means to direct limiting amounts of cytoplasmic PABP to a subset of viral mRNAs late in infection (7,8). Moreover, because PABP nuclear export is largely mRNA-driven in mammalian cells (12), and ICP27 promotes export of viral mRNAs (17), it is possible that the ICP27-PABP interaction may allow nuclear-retained PABP to be recruited and exported on these mRNAs, enabling their efficient translation. Specific binding of ICP27 to mRNAs that it translationally activates may be aided by another viral factor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We posited that elucidating this mechanism may provide insight into cellular mRNA-specific regulators because HSV-1 mRNAs are, like most cellular mRNAs, capped, polyadenylated, and translated via the canonical capdependent pathway described above. HSV-1 infection is accompanied by posttranslational modification of some initiation factors (9) and by relocalization of PABP to the nucleus (10, 11); however, similar modifications of the translational machinery occur in noninfected cells, for example, as a result of cellular stress (12,13).…”
Section: Significancementioning
confidence: 99%
“…PABPs are multifunctional RNA-binding proteins that regulate multiple aspects of mRNA translation and stability [67], including mediating retrotransposition of SINEs. SINEs are non-autonomous elements [8].…”
Section: Discussionmentioning
confidence: 99%
“…Kimura and Imamoto 84 give a detailed review of the importins. It was observed that Importin-α/ β was responsible in the transportation of PABPC1L (the cytoplasmic 1-like poly(A)-binding protein 60 that belong to a family of multifunctional proteins PABPs which regulate and stabilize the mRNA translation. The ranking of the PABC1L was found to be low after its suppression by ETC-1922159.…”
Section: Dicationmentioning
confidence: 99%
“…The role of RRM1 is also known from its association with PABC1L (see earlier discussion in the section of SCO1-WNT10B-X combinations). PABPC1L (as recorded by 51 ) or the cytoplasmic 1-like poly(A)-binding protein 60 , belong to a family of multifunctional proteins PABPs which regulate and stabilize the mRNA translation. They are observed to be helpful in the transportation of the mRNA also from the nucleus and there exists a nucleic version of PABP also 61 .…”
Section: Dicationmentioning
confidence: 99%